Investigation of the force effect of the vibrating working body of the slitter on the soil - Konstantinov, M.; Drozdov, S.; Mukhamedov, V.; Nuralin, B.; Galiev, M. (International Conference on Modern Trends in Manufacturing Technologies and Equipment: ICMTMTE 2020, 2020)
The theory of the force action of the working body of the slitter on the ground is considered. It is proposed to divide this force into four components: the force of cutting the material, the force of overcoming the friction forces acting on the ground, the force of cracking the material and the force of resistance of the ground environment. Theoretical dependences for determining the components of the tool's traction resistance when using vibration are proposed. As a result of theoretical and experimental studies, it was found that due to the vibration effect of the working body of the slot rod, the traction resistance is reduced by 13.8%. The decrease is due to changes in the physical and mechanical properties of the soil under the influence of directional vibrations. Рассмотрена теория силового воздействия рабочего органа продольно-резательного станка на грунт. Предлагается разделить эту силу на четыре составляющие: силу разрезания материала, силу преодоления сил трения, действующих на землю, силу растрескивания материала и силу сопротивления грунтовой среды. Предложены теоретические зависимости для определения составляющих тягового сопротивления инструмента при использовании вибрации. В результате теоретических и экспериментальных исследований было установлено, что за счет вибрационного воздействия рабочего тела пазового стержня тяговое сопротивление снижается на 13,8%. Уменьшение связано с изменением физико-механических свойств грунта под действием направленных колебаний.
Keywords: импакт-фактор 2020; скопус; зарубежное издание; дальнее зарубежье; зарубежные авторы; конференции; тяговое сопротивление; продольно-резательный станок